Do Uniforms Improve Patient Satisfaction? A Systematic Review of Attire-Related Perceptions and Service Quality Impacts - Tsalsa Dzikria Savira; Shanaz Hanani Tazuyyun; Jodii Arlan Kurnia; Kurnia Widyaningrum; Arina Salsabilla Haq (UNIVERSITAS NEGERI SURABAYA, 2026)
Objective: This systematic literature review synthesizes empirical evidence on how healthcare professional uniforms influence patient satisfaction and perceived service quality, while examining their strategic role in organizational value creation and competitiveness. Method: Studies published between 2010 and 2025 were identified through Scispace, PubMed, and Google Scholar. Following the PRISMA screening process, seven eligible studies were included for narrative synthesis. seven studies met the inclusion criteria and were included in the final narrative synthesis. Results: The included studies consistently reported that healthcare uniforms influenced perceptions of professionalism, trust, and role recognition, although preferences varied across clinical settings and patient characteristics. White coats were generally preferred in outpatient settings, whereas scrubs were favored in emergency and surgical contexts. Evidence also indicated that uniforms had limited direct influence on patient satisfaction, which was more strongly associated with communication quality, empathy, and responsiveness. Novelty: This review proposes a SERVQUAL-based framework distinguishing uniform-related perceptions of service quality from the determinants of actual patient satisfaction, while positioning healthcare uniforms as strategic service cues for organizational competitiveness.